Toxoplasma gondii: Detection by mouse bioassay, histopathology, and polymerase chain reaction in tissues from experimentally infected pigs - Garcia, João Luis; Gennari, Solange Maria; Machado, Rosângela Zacarias [UNESP]; Navarro, Italmar Teodorico (Elsevier, 2006)
In the present study, we evaluated three techniques, mouse bioassay, histopathology, and polymerase chain reaction (PCR) to detect Toxoplasma gondii infection in tissues from experimentally infected pigs. Twelve mixed breed pigs, seronegative for T. gondii using an indirect immunofluorescent antibody test (IFAT), were used. Ten pigs were infected with 4 × 104 VEG strain oocysts, and two were maintained as uninfected controls. Animals were killed 60 days pos infection. Muscle (heart, tongue, diaphragm, and masseter) and brain samples were collected to investigate the presence of T. gondii tissue cysts by the different assay methods. For the bioassay, samples of brain (50 g) and pool of muscle samples (12.5 g of tongue, masseter, diaphragm, and heart) were used. PCR was performed using Tox4 and Tox5 primers which amplified a 529 bp fragment. The DNA extraction and PCR were performed three times, and all tissue samples were tested individually (brain, tongue, masseter, diaphragm, and heart). For histopathology, fragments of tissues were fixed in 10% of buffered formal saline and stained with HE. Histopathological results were all negative. PCR showed 25/150 (16.6%) positive samples, being 17/120 (14.1%) and 8/30 (26.6%) from muscle, and brain tissues, respectively. Tissue cysts of T. gondii were identified by mouse bioassay in 54/98 (55.1%) samples, being 31/48 (64.6%) from muscle samples, and 23/50 (46.0%) from brain samples. Toxoplasma gondii isolation in muscle samples by mouse bioassay was higher than in PCR (P < 0.01). Results indicate that DNA from pig tissues interfered with 529-bp-PCR sensitivity, and mouse bioassay was better than PCR in detecting T. gondii in tissues from pigs. © 2006 Elsevier Inc. All rights reserved.
Keywords: Apicomplexa; deoxyribonucleic acid; DNA; HE; hematoxylin-eosin; Histopathology; IFA; IM; indirect immunofluorescence assay; intramuscular; Mouse bioassay; PCR; Pigs; polymerase chain reaction; Protozoa; Toxoplasma gondii; buffer; protozoal DNA; sodium chloride; animal experiment; animal model; animal tissue; bioassay; controlled study; diaphragm muscle; DNA determination; DNA extraction; experimental infection; female; heart muscle; histopathology; immunohistochemistry; male; masseter muscle; muscle tissue; nonhuman; oocyst; parasite identification; parasite isolation; priority journal; sample; sensitivity analysis; swine; tissue section; tongue; toxoplasmosis; Animals; Biological Assay; Brain; DNA, Protozoan; Female; Male; Mice; Muscles; Polymerase Chain Reaction; Random Allocation; Sensitivity and Specificity; Swine; Swine Diseases; Toxoplasma; Toxoplasmosis, Animal; Animalia; Sus scrofa